Brachial artery injury due to closed posterior elbow dislocation: case report☆ - Alberto Naoki Miyazaki; Marcelo Fregoneze; Pedro Doneux Santos; Guilherme do Val Sella; Caio Santos Checchia; Sergio Luiz Checchia (Revista Brasileira de Ortopedia, 2016)
An association between closed posterior elbow dislocation and traumatic brachial artery injury is rare. Absence of radial pulse on palpation is an important warning sign and arteriography is the gold-standard diagnostic test. Early diagnosis is essential for appropriate treatment to be provided. This consists of joint reduction and immobilization, along with urgent surgical restoration of arterial flow. Here, a case (novel to the Brazilian literature) of an association between these injuries (and the treatment implemented) in a 27-year-old male patient is reported. These injuries were sustained through physical assault.